Riequilibrare i rapporti globali Nord-Sud: Alexander Langer e la teorizzazione del debito ecologico - Clara BASSAN (Diacronie. Studi di Storia Contemporanea)
This article analyses the transnational action of the «North-South Campaign, Biosphere, Survive of people, Debt», an Italian initiative active from 1988 to 1993, and promoted by Alexander Langer together with different actors belonging to environmental activism, pacifist groups, feminist or cooperation of development organizations. This campaign triggered innovative and critical reflections on North-South relations, the global economic system, and developmental programmes from the perspective of environmental justice. Moreover, it encouraged a dialogue between Italian environmentalism and global-South ecologism. The alternative discourse about economic, ecological, and political relations between countries shifted the focus from the Third World debt to a more equal ecological debt. Besides these theoretical aspects, the campaign committed to the restitution of some Amazonian territories traditionally in use by the Indigenous community of Xavante and recently bought by the Agip Petroli Company. The article relies on the campaign documentation.